Translations of the Mountain: exploring natural phenomona through ephemeral drawings and intransigent matter in design - Allderman, Sarah (School of Architecture, Planning and Geomatics, 2017)
My interest this year was an architecture based on experience and how the architect rationalizes the complexities of the ineffable. With experience being such an intangible phenomena, whilst architecture is such an intransigent material, the process became about how to translate the one to the other through the process of drawing. By using Table Mountain as a site for exploration, the intangible experience of dwelling on the mountain was studied as an experience to be translated into architecture. This was explored through a process of cognitive and architectural drawings; ephemeral to tectonic details. The disser tation follows the process of landing on site, experiencing the space subconsciously through the intelligence of the body, and reflecting thereupon through cognitive drawing. The exploration follows the translation of these cognitive drawings into architectural drawings, in a way that returns to the experiential quality that which they originally depicted. Translating two-dimensional paper into three-dimensional imagined experience, which is embodied all the way through to the tectonic details. The process informs an architecture which allows the user 's mind to drift to the memory of the mountain, re-orientating themselves to their natural surroundings and enhancing their dwelling experience.